2019
DOI: 10.1101/522375
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effects of aging on neural signatures of temporal regularity processing in sounds

Abstract: Sensitivity to temporal regularity (e.g., amplitude modulation) is crucial for speech perception.Degradation of the auditory periphery due to aging and hearing loss may lead to an increased response gain in auditory cortex, with potential consequences for the processing of temporal regularities. We used electroencephalography recorded from younger (18-33 years) and older (55-80 years) adults to investigate how aging affects neural gain and the neural sensitivity to amplitude modulation in sounds.Aging was asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 110 publications
(185 reference statements)
0
3
0
Order By: Relevance
“…Adaptation to sound-level context or other properties of the acoustic environment -often referred to as adaptation to stimulus statistics 15,16,18 -requires that neurons represent stimulation history across several stimuli. For Experiment I and Supplementary Experiments A and B, we adapted experimental paradigms from our previous work on longer-term adaptation in the human auditory cortex 42,43 to investigate the extent to which stimulation history is reflected in adaptation of human brainstem responses. We observed that the Wave V of the auditory evoked potential -originating from the brainstem 41,[44][45][46][47] -peaked later when more clicks occurred within a preceding time window ("decelerating" sequence) compared to fewer clicks ("accelerating" sequence), despite an identical interval directly preceding each target click and identical sound levels (Experiments I and Supplementary Experiment A; Figures 1 and S1).…”
Section: Discussion Discussion Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adaptation to sound-level context or other properties of the acoustic environment -often referred to as adaptation to stimulus statistics 15,16,18 -requires that neurons represent stimulation history across several stimuli. For Experiment I and Supplementary Experiments A and B, we adapted experimental paradigms from our previous work on longer-term adaptation in the human auditory cortex 42,43 to investigate the extent to which stimulation history is reflected in adaptation of human brainstem responses. We observed that the Wave V of the auditory evoked potential -originating from the brainstem 41,[44][45][46][47] -peaked later when more clicks occurred within a preceding time window ("decelerating" sequence) compared to fewer clicks ("accelerating" sequence), despite an identical interval directly preceding each target click and identical sound levels (Experiments I and Supplementary Experiment A; Figures 1 and S1).…”
Section: Discussion Discussion Discussionmentioning
confidence: 99%
“…A prerequisite for adaptation to sound-level context is the capacity of neurons to represent the sound history over several stimuli in their activity patterns. To investigate whether the human brainstem is sensitive to sound history, we adapted a paradigm that has been successfully utilized to investigate adaptation of the human auditory cortex 42,43 . In Experiment I, normal-hearing younger adults (N=17) listened to click sequences presented at 60 dB sensation level (SL) that continuously "accelerated" and "decelerated": the click onset-to-onset interval decreased logarithmically from 60 ms to 10 ms and then increased back to 60 ms (Figure 1A).…”
Section: Human Brainstem Activity Human Brainstem Activity Human Brainstem Activity Human Brainstem Activity Is Is Is Is Sensitive To Senmentioning
confidence: 99%
See 1 more Smart Citation